The OSCE as a yardstick for multilateral security - Nadja Douglas (Stiftung Wissenschaft und Politik (SWP), 2025)
The European security order is dysfunctional and particularly affected by the crisis of multilateralism. The Organisation for Security and Cooperation in Europe (OSCE), founded as a forum for promoting cooperative security and standardsbased cooperation, today is an expression of the weakness of traditional multilateral institutions. The reporting system in the politico-military dimension of the OSCE is a seismograph for the change in norms and dynamics among participating States. However, it also shows that despite the changes at the political-strategic level and the politicization of the official agenda, the implementation of agreements at the technical-military level of the OSCE continues quite smoothly. This presents opportunities but also risks that the 57 participating States should be aware of.
Keywords: 320; crisis of multilateralism; Organisation for Security and Co-operation in Europe (OSCE); United Nations (UN) Charter; Helsinki Principles; Russia; war against Ukraine; North Atlantic Treaty Organization (NATO); confidence- and security-building measures (CSBMs); Code of Conduct on Politico-Military Aspects of Security (CoC); Vienna Document (VD) on CSBMs